PROBLEMS OF STANDARDIZING MODERN TOURISM TERMINOLOGY AND THE EXPERIENCE OF THE WORLD TOURISM ORGANIZATION (World Conference on Engineering and Technological Sciences, 2026)
This article analyzes the problems of standardizing modern tourism terminology and the experience of the World Tourism Organization based on a comprehensive scientific approach. The accuracy and uniformity of terms in tourism are substantiated as key factors determining the effectiveness of global communication. The formation of the terminological system, its linguistic and social factors, structural features, as well as the theoretical and practical significance of standardization are examined. In addition, existing problems and prospective solutions are analyzed based on international standards and UNWTO experience.
Keywords: Tourism, terminology, standardization, globalization, system, communication, UNWTO